Predictive validity for the clinical diagnosis of a new parent questionnaire, the CABI, compared with CBCL. (April 2020) - Cianchetti, Carlo; Faedda, Noemi; Pasculli, Marcello; Ledda, Maria Giuseppina; Diaz, Giacomo; Peschechera, Antonia; Craig, Francesco; Morelli, Federica; Balottin, Umberto; Guidetti, Vincenzo; Zuddas, Alessandro; Margari, Lucia
Background: The questionnaires completed by the parents give a first general information on the behavioral problems of the child–adolescent, as a useful orientation to the clinical evaluation. The Child and Adolescent Behavior Inventory (CABI) is a 75-item parent questionnaire, which explores a large number of problem areas. The study of its predictive validity for the clinical diagnosis, in comparison with the Diagnostic and Statistical Manual of Mental Disorders ( DSM )-oriented scales of the Child Behavior Checklist (CBCL), can assess whether its use may be advantageous. Material and Methods: Parents/caregivers of 462 children and adolescents responded to both CABI and CBCL as a preliminary routine investigation. The results were compared with those of diagnoses obtained after the completion of the usual clinical procedure. Results: Accuracy values (probability of correct classification) resulted high for both instruments and significantly better for CABI anxiety and attention-deficit hyperactivity disorder (ADHD) scales, and for CBCL oppositional defiant disorder (ODD) and conduct disorder (CD) scales; no significant difference was found for depression scales. All the areas under the curve (AUC) of the receiver operating characteristic analysis reached excellent values, suggesting a very good predictive ability of the five scales of the two instruments. The comparison of AUC showed the CABI's anxiety and ADHD scales to give significantly higher values than those of CBCL, indicating that these two scales have a better predictive ability. Conclusion: The study indicates a very good comparative (vs CBCL) and predictive validity of the CABI, suggesting an advantage in the use of this shorter questionnaire, available for free use both for clinical practice and supposedly for screening and epidemiological evaluations.